The Effect of Using Task Based Method towards Students' Listening Skill at The Seventh Grade Students of MTs Al-Ihya Kaduronyok - Capriati, Dian (Universitas Mathla'ul Anwar Banten, 2018)
This research paper aims to investigate the effect of using task based methodin improving students listening skill at the seventh grade students of MTs Al-Ihya Kaduronyok. The research paper employs the quantitative research design with the characteristic of an experimental study. It uses the same learning material both in experimental and control class. The data are obtained from 6 sessions of classroom activity. The researcher uses quantitative as the method of her research because the research designed as ‘the scientific method’ which can be defined as a test under controlled conditions that is made to demonstrate a known truth or examine the validity of a hypothesis. The findings reveal that using task based method is helpful and easy to conduct. In addition, this method can improve students’ listening skill. In relation to the responses on the method, it is found that the students respond the method positively. Based on the findings of this research, it can be shown through computing t-test the researcher got t-count (14.38) is higher than t-table (1.671). It means, there is significant effect of using task based method in teaching listening.